CHEMICAL COMPOSITION AND NUTRITIONAL VALUE OF MINCED MEAT - Eshmuratov Marat Tangatarovich; DJuldasbaeva Azada Oktamovna (American Journals, 2023)
In this article we will talk about the structure of meat and meat products.The preparation of meat and milk, as well as their processed products, are of great importance in people's daily lives. In the rational nutrition of people there are no products that replace them. Consequently, the demand and demand for meat, milk and products from them is growing every day.
Keywords: meat, food, Proteins, fats, carbohydrates